An Assessment of Solid Waste Management Generated in Eziobodo Community, Imo State, Nigeria - Nkeleme Emmanuel Ifeanyichukwu; Winston Shakantu; Nwabueze Micheal Anosike; Achigbu Onyemaeze Ikenna (Novel Perspectives of Engineering Research Vol. 3, 2021)
Solid waste management is a major problem that has reached alarming proportions requiring drastic measures. The increasing difficulty in managing wastes in Nigeria has become one of the most intractable environmental issues. There is an unprecedented increase in the rate of waste generated by the residents. The cardinal aim of the study is to “ascertain the assessment of solid waste management generated in Eziobodo community, Owerri West, Imo State, Nigeria”. To achieve this aim, 140 copies of questionnaires were administered to the residents of Eziobodo community selected at random. Of these, 112 copies of the questionnaire (80.0%) were returned and analyzed using descriptive statistics. Data from the questionnaires were analyzed by simple frequency and presented by percentage. The study revealed among others that: residential buildings account for the highest generation source of solid waste in the community and the solid waste was predominantly nylon/nylon bags/ nylon sachets; food waste, plastic can/rubbers arranged in their order of severity. Consequently, the effect of the solid waste in the community was; wide and easy spread of disease vectors, soil pollution, and easy breed of flies, rats, and mosquitoes. The survey revealed that the spread and causing of disease is the commonest effect of poor waste management in the community. Hence the study recommends, sorting of solid waste before dumping, provision of adequate Skips and dustbins, and ensuring regular collection of wastes. Finally, Potential for a sustainable approach to the management of solid waste such as recycling, reuse, energy recovery, and waste reduction.